Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1002/tea.3660310206
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐age study of the understanding of five chemistry concepts

Abstract: A sample of 100 students from junior high school physical science, high school chemistry, and introductory college chemistry were examined for understanding of five chemistry concepts. The concepts addressed were chemical change, dissolution of a solid in water, conservation of atoms, periodicity, and phase change. The amount of experience with the concepts (grade level) and reasoning ability (developmental level) were examined as possible sources of variation in student understanding. Differences in understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
24

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(165 citation statements)
references
References 23 publications
4
137
0
24
Order By: Relevance
“…Other studies have similarly found that few students tend to use atomic or molecular explanations for chemical phenomena (Abraham, Williamson, & Westbrook, 1994;Hesse & Anderson, 1992). Moreover, students might demonstrate a connected but alternative understanding of a scientiÞc phenomenon at the macroscopic and molecular levels.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 94%
“…Other studies have similarly found that few students tend to use atomic or molecular explanations for chemical phenomena (Abraham, Williamson, & Westbrook, 1994;Hesse & Anderson, 1992). Moreover, students might demonstrate a connected but alternative understanding of a scientiÞc phenomenon at the macroscopic and molecular levels.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 94%
“…It has been examined in terms of scope validity with the expert group formed by teachers and academic members. Such procedures increase the validity and reliability of the test [1,47].…”
Section: Reviewing the Test İtemsmentioning
confidence: 99%
“…The studies we will review included spatial abilities as one of the cognitive factors that may be relevant to the mastery of chemistry concepts. Other cognitive factors that have been considered by correlational research on chemistry learning included formal reasoning skills (Abraham & Westbrook, 1994;Chandran, Treagust, & Tobin, 1987;Haidar & Abraham, 1991;Keig & Rubba, 1993;Niaz, 1987Niaz, , 1988Niaz, , 1989Niaz & Robinson, 1992;Staver & Halsted, 1985), proportional reasoning skills (Anamuah-Mensah, Erickson, & Gaskell, 1987), field dependence/independence (Niaz & Lawson, 1985), and memory capacity (Niaz, 1988(Niaz, , 1989Niaz & Lawson, 1985;Niaz & Robinson, 1992). To narrow the scope of this article and focus on the visual aspect of chemistry learning, we review key findings of the correlational studies regarding chemistry learning and spatial abilities.…”
Section: To What Degree Do Individual Differences In Visuospatial Abimentioning
confidence: 99%